2002
DOI: 10.1007/s00520-002-0377-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescription for fever episodes in hospice patients

Abstract: Bacterial infection usually plays an important part in the fever episodes that are common in patients in the hospice palliative care unit. The physicians' attitude to use of antibiotics in such cases is usually complex. We retrospectively studied 535 admissions to a hospice and palliative care unit in a medical center in Taiwan. Ninety-three fever episodes (16.7%) were identified among these admissions, and 79 fever episodes (84.9%) were treated with antibiotics. The Karnofsky performance status (KPS), verbal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 16 publications
0
33
0
10
Order By: Relevance
“…6,[8][9][10][11][12]14 Six studies included only cancer patients. 8,[12][13][14][15][16] Four studies included all primary diagnoses requiring palliative care or consult.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6,[8][9][10][11][12]14 Six studies included only cancer patients. 8,[12][13][14][15][16] Four studies included all primary diagnoses requiring palliative care or consult.…”
Section: Resultsmentioning
confidence: 99%
“…8,[12][13][14][15][16] Four studies included all primary diagnoses requiring palliative care or consult. 6,7,9,10 One study included only dementia patients. 11 Only one study reported prophylaxis as an indication for antimicrobial prescription, citing use in two patients for traumatic urinary catheter insertion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…오히려 부종이나 흉막 삼출액, 호흡곤란, 객담 등의 증상이 더 악화될 수 있으며, 특히 흉막 삼출액 증상이 심해졌다는 보고가 있다 (6). 그 외에도 말기환자가 감염증상이 있을 때 흔 히 항생제를 처방하고 있으나, 생명연장에 대한 기대는 논쟁의 여지가 있다 (7,8). 말기환자의 항생제 사용에 대 한 연구에서 환자의 64∼84%가 항생제가 처방되었고 (9-11), 국내연구에서 55%는 증상개선이 없었으며, 15% 정도만 증상이 개선되었다 (9,10).…”
Section: 연구의 필요성unclassified